Maraknya Pengangguran dikalangan Pemuda - hananah, nuni (Maliki Interdisciplinary Journal, 2025)
Indonesia has many unemployed young people. Even when we encounter cities in Indonesia, there must be many unemployed young people, especially in remote areas far from the capital city. This unemployment not only affects the young people themselves but also their families, the environment and the country of Indonesia. This article aims to analyze the Causes of Unemployment among young people. This study also aims to analyze the Impact of Unemployment and Government Solutions in dealing with the rampant unemployment among young people. By using a literature review approach, it is hoped that this article can provide deeper insight into the rampant unemployment among young people in order to create young people with integrity, quality and the golden generation of Indonesian youth. The results of the study have made Indonesia the second largest country with the highest unemployment rate in ASEAN (Association of Southeast Asian Nations). The results of the Sakernas survey stated that the number of unemployed in Indonesia has reached 7.89 million people from a total workforce of 147.71 million people.This issue still requires special attention from various parties. Youth unemployment is a global problem that requires urgent and comprehensive solutions